Removal of heavy metal ions from mixed solutions via polymer-enhanced ultrafiltration using starch as a water-soluble biopolymer - Nurul Huda, Baharuddin (John Wiley and Sons Inc., 2016)
Link to publisher's homepage at http://onlinelibrary.wiley.com/